(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2022)
Al-Magh?z? (war) and al-Siyar (history) are historical narrations about military campaigns launched by Prophet Muhammad (PBUH) during his lifetime. Hadith scholars of the past were indubitably flexible in their authentication of al-Magh?z? and al-Siyar. Narrations which are of weak status (da??f) are accepted as long as they are not related to fundamental precepts and rules of Islam. However, narrations of al-Magh?z? and al-Siyar are not accepted if and when they are contrary to other religious authorities. While there are various ways of authentication in this regard, this research seeks to discern and investigate a methodology of evaluating the authenticity and acceptability of al-Magh?z? and al-Siyar by relying on the Quran as a benchmark. This research finds the method, which has been in practice since the days of the companions, may be used apparently in two scenarios. Firstly, hadith scholars shall reject the narrations of al-Magh?z? and al-Siyar when they unequivocally contradict verses of the Quran. Secondly, ?adith scholars shall equally reject narrations of al-Magh?z? and al-Siyar when they are not in line with the context of verses of the Quran. This research also demonstrates that, in the course of the process, hadith scholars shall not summarily reject the impugned narrations of al-Magh?z? and al-Siyar unless the respective discrepancies cannot be ultimately resolved and adequately explained. Methodologically, apart from depending heavily on library research methodology, inductive and deductive methods are concurrently used in this research to analyse the data collated from various sources of reference, which were referred to by hadith scholars in their criticisms of al-Magh?z? and al-Siyar. Al-Magh?z? (peperangan) dan al-Siyar (sejarah) ialah riwayat yang berkaitan dengan kisah peperangan pada zaman Nabi Muhammad SAW. Tidak dinafikan bahawa ulama silam memberikan kelonggaran untuk menerima riwayat al-Magh?z? dan al-Siyar yang daif selagi tidak berkaitan dengan akidah dan hukum. Namun begitu, ulama juga menetapkan bahawa riwayat al-Magh?z? dan al-Siyar tidak diterima jika bercanggah dengan dalil lain. Antara kaedah yang mereka gunakan adalah menjadikan al-Quranul Karim sebagai neraca untuk menilai ketepatan riwayat al-Magh?z? dan al-Siyar. Kajian ini menganalisis metodologi sarjana hadis dalam mengaplikasikan kaedah ini. Metodologi yang akan digunakan dalam kajian ini ialah metodologi perpustakaan. Metodologi deduktif dan induktif digunakan untuk menganalisis data yang diperoleh daripada rujukan hadis ketika melakukan kritikan terhadap riwayat al-Magh?z? dan al-Siyar. Kajian mendapati bahawa kaedah menjadikan al-Quran sebagai neraca dalam mengkritik riwayat al-Magh?z? dan al-Siyar telah pun digunakan oleh sarjana hadis sejak zaman sahabat lagi. Kaedah ini juga diaplikasikan dalam dua keadaan. Pertama, sarjana hadis menolak riwayat al-Magh?z? dan al-Siyar yang bercanggah dengan ayat al-Quran secara jelas. Kedua, mereka menolak riwayat al-Magh?z? dan al-Siyar yang tidak selari dengan konteks ayat al-Quran. Kajian ini juga membuktikan bahawa sarjana hadis tidak akan menolak riwayat al-Magh?z? dan al-Siyar melainkan apabila percanggahan tersebut tidak dapat diharmonikan.